The Influence Of Lumbar Support On Muscle Activities During Seated Computer Work - Muhammad Syahid, Mohd Suhaimi (2025)
Musculoskeletal disorders (MSDs) are a prevalent concern among individuals who spend prolonged periods seated at computers, particularly in office and academic environments. This study aims to investigate the impact of lumbar support on reducing the incidence of MSDs among computer users. Utilizing a randomized controlled trial (RCT) design, the research examines the efficacy of lumbar support by comparing muscle activity levels and comfort among participants with and without lumbar support. A total of 15 participants, including students and administrative staff from the University Malaysia Pahang Al-Sultan Abdullah (UMPSA), were recruited for this study. Each participant completed seated computer work tasks in two conditions: with lumbar support and without lumbar support. Objective assessments of muscle activity were conducted using surface electromyography (sEMG) to measure muscle activity in the lumbar and thoracic regions, while heart rate, perceived exertion, and typing performance were evaluated using standardized protocols. The study was conducted in the ergonomic laboratories at UMPSA, which were designed as workstations. The process included obtaining participant informed consent, conducting a demographic interview, explaining the process, collecting data, and performing data analysis to determine the results of the study. Quantitative data analysis involved paired t-tests using SPSS. The results indicated significant reductions in muscle activity in both the lumbar and thoracic regions when participants used lumbar support, highlighting its effectiveness in reducing muscle strain and promoting better posture. Perceived exertion also significantly decreased with lumbar support, reflecting enhanced physical comfort during seated tasks. However, heart rate showed no significant differences between conditions, suggesting that lumbar support primarily influences musculoskeletal factors. Typing speed improved slightly with lumbar support, while typing accuracy remained unchanged.